Dental health education game based-on IRVO model in augmented reality technology - Gita Indah Hapsari; Giva Andriana Mutiara; Roy Chaidir (JURNAL INFOTEL, 2022)
Public Dental health must be maintained from an early age. However, it is not easy to make the children interested, understand, and aware of dental health. This paper discussed alternative methods for educating the children using IRVO model in augmented reality technology-based educational games. The game was built from several materials consisting of dental health education recommended by the dentist. Some of the interactions represented in the game application consist of point of view, selection and release, event creation, and manipulation. This educational game is implemented using the 3DS Max and D-Fusion Studio. This game has been approved for counsellors such as dentists, nurses, community health workers, and children. According to the resulting test, more than 75% of the dentists and children are interested in using this game and declared that they could use this application easily.